2016
DOI: 10.1002/jhet.2640
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Bioactivity Evaluation of Novel 3‐(Substituted Phenoxy)‐6‐Methyl‐4‐(3‐Trifluoromethylphenyl) Pyridazine Derivatives

Abstract: Using 3‐(4‐cyano phenoxy)‐6‐methyl‐4‐(3‐trifluoromethylphenyl) pyridazine (compound A) as a leading compound, a total of 24 novel 3‐(substituted phenoxy)‐6‐methyl‐4‐(3‐trifluoromethylphenyl) pyridazine derivatives containing two electron‐withdrawing groups on the benzene ring (acylamine and oxime ether) were synthesized. Their herbicidal, insecticidal activities were bioassayed, and the herbicidal activity of compound CD-2 against Brassica campestris was 97.6% at 300 g/ha, which was better than the commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Zou et al designed and synthesized a series of 3-(substituted phenoxy)-6-methyl-4-(3-trifluoromethyl-phenyl) pyridine derivatives that exhibited significant herbicidal and insecticidal activities . Notably, compounds 58 and 59 (Figure ) demonstrated over 95% insecticidal activity against A. laburni Kaltenbach at 200 mg/L.…”
Section: Oxime Ether Derivatives With Insecticidal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Zou et al designed and synthesized a series of 3-(substituted phenoxy)-6-methyl-4-(3-trifluoromethyl-phenyl) pyridine derivatives that exhibited significant herbicidal and insecticidal activities . Notably, compounds 58 and 59 (Figure ) demonstrated over 95% insecticidal activity against A. laburni Kaltenbach at 200 mg/L.…”
Section: Oxime Ether Derivatives With Insecticidal Activitymentioning
confidence: 99%
“…Zou et al designed and synthesized a series of 3-(substituted phenoxy)-6-methyl-4-(3-trifluoromethyl-phenyl) pyridine derivatives that exhibited significant herbicidal and insecticidal activities. 59 Notably, compounds 58 and 59 (Figure 7) demonstrated over 95% insecticidal activity against A. laburni Kaltenbach at 200 mg/L. The synthesis route for these compounds commenced with the conversion of 3-chloro-6methyl-4-(3-(trifluoromethyl)phenyl)pyridazine to aromatic ether derivative 56 through nucleophilic substitution.…”
Section: ■ Data Collectionmentioning
confidence: 99%
“…Among 25 mode-of-action groups of commercial herbicides classified by the Herbicide Resistance Action Committee in 2021 (, accessed on June 07, 2023), only seven PDS-inhibiting herbicides have been commercialized, such as beflubutamid, diflufenican ( BF ), and picolinafen (Figure ). BF is a preemergence and postemergence herbicide used to control broadleaf and grass weeds in winter cereals at a dosage of 50–250 g a.i./ha. , BF is also characterized by low mobility and long-lasting effects as it is readily absorbed by soil. , However, with the long-term and frequent use of PDS-targeting herbicides, herbicide-resistant weeds have constantly emerged. , In recent years, few studies have been reported on the development of herbicides targeting PDS. , To effectively avoid or alleviate PDS-inhibiting herbicide resistance, developing novel molecules with high efficacy and low toxicity based on PDS is necessary.…”
Section: Introductionmentioning
confidence: 99%